2020
DOI: 10.21203/rs.3.rs-130885/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long Non-Coding RNA CCDC183-AS1 Acts as a miR-589-5p Sponge to Promote The Progression of Hepatocellular Carcinoma Through Regulating SKP1 Expression

Abstract: Background: Hepatocellular carcinoma (HCC) is a common type of malignant human cancer with high morbidity and poor prognosis, causing numerous deaths per year worldwide. Growing evidence has been demonstrated that long non-coding RNAs (lncRNAs) are closely associated with hepatocarcinogenesis and metastasis. However, the roles, functions, and working mechanisms of most lncRNAs in HCC remain poorly defined.Methods: Real-time quantitative polymerase chain reaction (qRT-PCR) was used to detect the expression leve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…For instance, circRNA microarray analysis showed that hsa_circ_0016070 is correlated with pulmonary arterial hypertension in patients with chronic obstructive pulmonary disease [18]. circDNMT3B overexpression reduces the retinal acellular capillary number and attenuates visual impairment in diabetic rats [19]. In the present study, the expression of circ-UBAP2 was overexpressed in the vitreous humor of DR patients and HG-treated hRMECs, which was consistent with a previous study [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, circRNA microarray analysis showed that hsa_circ_0016070 is correlated with pulmonary arterial hypertension in patients with chronic obstructive pulmonary disease [18]. circDNMT3B overexpression reduces the retinal acellular capillary number and attenuates visual impairment in diabetic rats [19]. In the present study, the expression of circ-UBAP2 was overexpressed in the vitreous humor of DR patients and HG-treated hRMECs, which was consistent with a previous study [20].…”
Section: Discussionsupporting
confidence: 91%
“…miR-589-5p was predicted and confirmed to be a potential target of circ-UBAP2. To date, miR-589-5p has been mainly investigated in oncogeneses, such as hepatocellular carcinoma [19,20], renal cell carcinoma [21], and laryngocarcinoma [22]. However, it has not been sufficiently explored in DR. Zou et al [23] confirmed that miR-589-5p targets the oxidative damage gene XPC-rs2229090 C allele in the age-related cataract (ARC), which might increase the risk of ARC.…”
Section: Discussionmentioning
confidence: 99%
“…MYOSLID promotes the progression of osteosarcoma through the miR-1286/RAB13 axis [59], and MYOSLID plays a key role in stomach neoplasm through the miR-29c-3p-mcl-1 axis [60], but it has not been reported in CC. CCDC183-AS1 enhances hepatocellular carcinoma progression by regulating SKP1 expression via MIR-589-5P [61]. e miR-3127-5p/E2F7 axis increases CC cell proliferation and migration, and LINC00174 plays a role in this process [62].…”
Section: Discussionmentioning
confidence: 99%
“…For miRNA, reverse transcriptions were performed using the Mir-X miRNA First-Strand Synthesis Kit (Takara, Japan). Real-time qPCR was performed as described previously [19]. U6 and GAPDH were used as endogenous controls for the detection of circRNA, miRNA, and mRNA expression, respectively.…”
Section: Quantitative Pcrmentioning
confidence: 99%